2012
DOI: 10.1088/0741-3335/54/12/124047
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of plasma turbulence in scrape-off layer conditions: the GBS code, simulation results and code validation

Abstract: Based on the drift-reduced Braginskii equations, the Global Braginskii Solver, GBS, is able to model the scrape-off layer (SOL) plasma turbulence in terms of the interplay between the plasma outflow from the tokamak core, the turbulent transport, and the losses at the vessel. Model equations, the GBS numerical algorithm, and GBS simulation results are described. GBS has been first developed to model turbulence in basic plasma physics devices, such as linear and simple magnetized toroidal devices, which contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
295
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(299 citation statements)
references
References 82 publications
4
295
0
Order By: Relevance
“…23 At the top and at the bottom of the limiter, these are, in normalized units, The system of equations presented in this paper considers, with respect to the system of equations presented in Ref. 7, an arbitrary magnetic field configuration. The modulus of the magnetic field B, the divergence of the unitary magnetic field vector r Á b, the differential operators r k , r 2…”
Section: A Fluid Moment Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 At the top and at the bottom of the limiter, these are, in normalized units, The system of equations presented in this paper considers, with respect to the system of equations presented in Ref. 7, an arbitrary magnetic field configuration. The modulus of the magnetic field B, the divergence of the unitary magnetic field vector r Á b, the differential operators r k , r 2…”
Section: A Fluid Moment Equationsmentioning
confidence: 99%
“…Then, a flux-driven model is preferred over a fixed-gradient model because the former is closer to experimental conditions, where profiles result from a balance between sources and losses and are a-priori unknown, exhibiting richer physics such as the appearance of avalanches 6 and self-consistent interactions between the background and the fluctuations. Such fluid flux-driven simulations have emerged, [6][7][8][9] allowing to simulate SOL plasma turbulence and shedding light on the crucial physical phenomena at play in this region. In a recent publication, 10 it has been shown that the gradient-removal theory is able to predict relatively well the sustainable pressure gradient inside the SOL for 3D fluid simulations in limited geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The model is described fully in Ref. 22. The use of a fluid model is justified by that fact that, in the tokamak scrape-off layer, collisions play an important role and kinetic effects, such as trapping, are less important.…”
Section: Drift Reduced Braginskii Equations and Boundary Conditionsmentioning
confidence: 99%
“…In this section, we describe non-linear 3D electromagnetic simulations of scrape-off layer turbulence carried out with GBS, 22 an initial value, global 3D non-linear code which advances in time the five scalar fields in Eqs. (1)- (5).…”
Section: Non-linear Simulations and Ideal Ballooning Thresholdmentioning
confidence: 99%
See 1 more Smart Citation